Assessing Health-Related Quality of Life Among Survivors of Testicular Cancer: A Systematic Review - Rovito, Michael J. (Am J Mens Health, 2021)
This study aimed to determine if the current health-related quality of life (HRQoL) tools created for survivors of testicular cancer are collecting the highest quality of data via a two-step methodological critique of both the seminal studies that produced a survivor of testicular cancer HRQoL tool (Phase 1) and the actual tool itself (Phase 2). It is the goal of this current article to present and discuss Phase 1. A systematic review aimed to assess the methodological quality of studies conducted to create instruments used to measure survivors of testicular cancer HRQoL. Five reviewers independently assessed each study with the 20-item Appraisal Tool for Cross-Sectional Studies (AXIS). Inter-rater agreement and Fleiss’ kappa was also assessed to ensure consistency in reported scores. Assessments for the EORTC QLQ-TC 26 and CAYA-T studies were low (AXIS 52.5%; IRA 95%; κ = 0.779) and fair (AXIS 65%; IRA 80%; κ = 0.599), respectively. Critical appraisal of the scales included issues within the three core AXIS domains. Primary concerns related to sampling methodology and the lack of a qualitative component of their core conceptual development phase. Both reviewed seminal studies have significant methodological concerns that question the tools’ quality. Next steps include extensive appraisal of the psychometric properties of the EORTC QLQ TC-26 and the CAYA-T to complete the comprehensive review. Accurate and reliable data are necessary to understand survivor of testicular cancer HRQoL and assist in building the bridge of communication between health care professionals and survivors to help to improve patient outcomes.